Sequence analysis of porcine kobuvirus VP1 region detected in pigs in Japan and Thailand - Okitsu,S. (Springer Netherlands, 2015)
Porcine kobuvirus is a new candidate species of the genus Kobuvirus in the family Picornaviridae, and information is still limited. The identification of porcine kobuvirus has been performed by the sequence analyses of the 3D region of the viruses. Therefore, the purpose of this study was to characterize the molecular properties of VP1 nucleotide sequences of the porcine kobuviruses isolated from porcine stool samples in Japan during 2009 and Thailand between 2006 and 2008. In addition, previous identification of a unique porcine kobuvirus; Japanese H023/2009/JP, which is a bovine kobuvirus-like strain based on sequence analysis of the 3D region, was also included in this study. All of the strains were amplified by the VP1-specific primer pair: the amplicons were subjected to direct sequencing and compared with the VP1 nucleotide sequences of reference strains. The VP1 sequences of strains from the GenBank database revealed high nucleotide sequence identity at 84.3-100%. On the other hand, the nucleotide identities among the 15 porcine kobuvirus strains analyzed in this study ranged from 78.8 to 99.8%. The results revealed that diversity of the strains in this study were higher than those of the strains in previous studies. Furthermore, it was found that the VP1 region of the bovine kobuvirus-like strain, H023/2009/JP, clustered with nine porcine kobuvirus strains that were isolated in Thailand and Japan. Since this strain was previously found to be closely related to bovine kobuviruses in the 3D gene region, it may be a natural recombinant. © Springer Science+Business Media, LLC 2011.